Comparison of patients' needs for information on prostate surgery with printed materials provided by surgeons. Issue 1 (March 1995) - Meredith, P; Emberton, M; Wood, C; Smith, J
Abstract : OBJECTIVES--To identify strengths, weaknesses, and omissions in existing leaflets and factsheets on prostatectomy given by surgeons to patients. DESIGN--Comparison of content of leaflets and factsheets with patients' needs and discontents in a questionnaire survey as part of the national prostatectomy audit. SETTING--All NHS and independent hospitals performing prostatectomy in four health regions. SUBJECTS--87 surgeons, 53 of whom used printed material to inform patients about their operations; a total of 25 different factsheets being used. 5361 men undergoing prostatectomy were sent a closed response questionnaire about their treatment; 4226 men returned it completed. A random sample of 2000 patients was asked for further comments, of whom 807 supplied pertinent comments. MAIN MEASURES--Content of the 25 factsheets compared with patients' needs identified in the questionnaires. RESULTS--Much of the information distributed had considerable shortcomings: it lacked uniformity in form and content, topics of relevance to patients were omitted, terminology was often poor, and patients' experience was at variance with what their surgeons said. For example, only one factsheet discussed the potential consequences of malignancy. Patients wanted more information on prostate cancer (1250(29%)) and some thought that the explanation of biopsy results was inadequate (29(4%)). Only six factsheets discussed the possible changes in sexual sensation after transurethral resection of the prostate, stating that patients would feel no change. However, 1490(35%) patients reported a change and 500(12%) were worried about it. CONCLUSION--Current standards of printed information do not meet the needs and requirements of patients undergoing prostatectomy.